2017
DOI: 10.1016/j.tcs.2016.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Design tools for reporter strands and DNA origami scaffold strands

Abstract: Self-assembly using DNA origami methods requires determining a route for the scaffolding strand through the targeted structure. Here we provide strategies and software tools for determining optimal routes for reporter or scaffolding strands through graph-like (balland-rod) constructs. The approach applies to complex constructs, for example arbitrary geometric embeddings of graphs rather than surface meshes, lattice subsets, and meshes on higher genus surfaces than spheres. The software notably allows the user … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Eulerian tours have previously featured in experimental and theoretical considerations of DNA [3,8,18,25,35] and protein self-assembly [14,21]. Similarly, topological constraints have been implicitly considered in previous works [3,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eulerian tours have previously featured in experimental and theoretical considerations of DNA [3,8,18,25,35] and protein self-assembly [14,21]. Similarly, topological constraints have been implicitly considered in previous works [3,6].…”
Section: Discussionmentioning
confidence: 99%
“…A fundamental topological constraint when employing a circular strand for assembly is that the strand routing must be unknotted. In a recent paper, Ellis-Monaghan et al [8] have shown the scaffold routings of Benson et al [3] can be knotted on highergenus surfaces. In Figure 1, we present another example of a knotted Chinese-postmantour/Eulerian-tour routing on a triangulated torus.…”
Section: Introductionmentioning
confidence: 99%
“…Often, an important consideration in determining reporter or scaffolding strand walks is assuring that the result is not knotted. The authors of [7] observed that knotted walks can result from A-trails (non-crossing Eulerian circuits) in toroidal meshes, while [14] characterizes knotted and unknotted A-trails in toroidal meshes and [12] gives an an approximation algorithm for unknotted walks in surface triangulations. In [1] the authors restrict to spheres to assure unknotted routes.…”
Section: A Short Proof That Reporter Strand Walks Existmentioning
confidence: 99%
“…At its most basic level, the design objective for DNA origami assembly of a graph-like structure is a strategy with the scaffolding strand following a single walk that traverses every edge at least once, with any edges that are traversed more than once visited exactly twice, in opposite directions (because DNA strands in a double helix are oppositely directed), and without separating or crossing through at a vertex. See [1,5,7] for further work on routing scaffolding strands.…”
Section: Introductionmentioning
confidence: 99%
“…If the surface is a sphere, as in [5], all A-trails in the target structure are necessarily unknotted, and so may be used as routes for the unknotted scaffolding strand. On higher-genus surfaces such as the torus, this is no longer the case [8].…”
Section: Introductionmentioning
confidence: 99%